2007
DOI: 10.1007/s11664-007-0283-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cross-Interaction between Ni and Cu on Growth Kinetics of Intermetallic Compounds in Ni/Sn/Cu Diffusion Couples during Aging

Abstract: The solid-state, cross-interaction between the Ni layer on the component side and the Cu pad on the printed circuit board (PCB) side in ball grid array (BGA) solder joints was investigated by employing Ni(15 lm)/Sn(65 lm)/Cu ternary diffusion couples. The ternary diffusion couples were prepared by sequentially electroplating Sn and Ni on a Cu foil and were aged isothermally at 150, 180, and 200°C. The growth of the intermetallic compound (IMC) layer on the Ni side was coupled with that on the Cu side by the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The growth of (Cu,Ni) 6 Sn 5 at temperatures ranging from 150°C to 200°C follows approximately parabolic kinetics. 10,11 Upon current stressing, the Cu flux across the Sn (J Cu ) is determined by both the diffusion term due to the chemical potential gradient (J Cu chem ) and the drift term due to the electron momentum transfer effect (J Cu em ). It is clear that the direction and magnitude of the electric current play dominant roles in J Cu em ; thus affecting the growth of Cu-containing IMCs at the Ni-side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of (Cu,Ni) 6 Sn 5 at temperatures ranging from 150°C to 200°C follows approximately parabolic kinetics. 10,11 Upon current stressing, the Cu flux across the Sn (J Cu ) is determined by both the diffusion term due to the chemical potential gradient (J Cu chem ) and the drift term due to the electron momentum transfer effect (J Cu em ). It is clear that the direction and magnitude of the electric current play dominant roles in J Cu em ; thus affecting the growth of Cu-containing IMCs at the Ni-side.…”
Section: Discussionmentioning
confidence: 99%
“…One of these reliability concerns results from the so-called crossinteraction between Cu and Ni. [1][2][3][4][5][6][7][8][9][10][11] It was recently reported that both Cu and Ni atoms can diffuse across the entire solder (hundreds of microns) to opposite sides of the sandwich structure in a very short time (a few seconds) during soldering. [1][2][3][4][5][6][7][8] The diffusion of Cu to the Ni-side can form a single layer of (Cu,Ni) 6 Sn 5 or a bilayer of (Cu,Ni) 6 Sn 5 and (Ni,Cu) 3 Sn 4 over the Ni pad, 1-8 resulting in a brittle solder/pad interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial reactions in the Ni/Snbased solder/Cu combination after annealing were reported and attributed to the difference in the Cu or Ni concentrations between the Ni and the Cu pads. [1][2][3][4][5][6] Under such conditions, the interfacial reactions were greatly accelerated and the thermal stability of the Cu UBM degraded due to the formation of (Cu,Ni) 6 Sn 5 intermetallic compounds (IMCs). 1,2,5,6 Electromigration behavior of the Ni/Sn-based solder/Cu combination has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…During joint structure fabrication or subsequent operation, an appreciable amount of Cu can diffuse through the entire solder to the Ni side, [1][2][3][4][5][6][7][8][9][10][11] where it nucleates as a very brittle (Cu,Ni) 6 Sn 5 /(Ni,Cu) 3 Sn 4 bilayer structure. 8,12 The cross-diffusion of Cu to the opposite Ni is known as an up-hill diffusion process, in which Cu diffuses from a region with lower Cu concentration (C Cu ) (less than 0.1 wt.% for solid solder at 150°C 13 ) to one with higher C Cu [more than 20 wt.% for the (Cu,Ni) 6 Sn 5 phase formed on the Ni side].…”
Section: Introductionmentioning
confidence: 99%